Hemolysis pathways during storage of erythrocytes and inter-donor variability in erythrocyte morphology - Melzak, Kathryn; Spouge, John L.; Böcker, Clemens; Kirschhöfer, Frank; Brenner-Weiß, Gerald; Bieback, Karen (Transfusion medicine and hemotherapy, 2021)
Background: Red blood cells (RBCs) stored for transfusions can lyse over the course of the storage period. The lysis is traditionally assumed to occur via the formation of spiculated echinocyte forms, so that cells that appear smoother are assumed to have better storage quality. We investigate this hypothesis by comparing the morphological distribution to the hemolysis for samples from different donors. Methods: Red cell concentrates were obtained from a regional blood bank quality control laboratory. Out of 636 units processed by the laboratory, we obtained 26 high hemolysis units and 24 low hemolysis units for assessment of RBC morphology. The association between the morphology and the hemolysis was tested with the Wilcoxon-Mann-Whitney U test. Results: Samples with high stomatocyte counts (p = 0.0012) were associated with increased hemolysis, implying that cells can lyse via the formation of stomatocytes. Conclusion: RBCs can lyse without significant echinocyte formation. Lower degrees of spiculation are not a good indicator of low hemolysis when RBCs from different donors are compared.